2016
DOI: 10.17522/balikesirnef.277730
|View full text |Cite
|
Sign up to set email alerts
|

İlköğretim Matematik Öğretmen Adaylarının Üçgenlerin Öğretiminde Geometrik İspatları Kullanabilme Becerileri

Abstract: -In this study, it was aimed to reveal prospective elementary mathematics teachers' abilities of using geometric proofs in triangle teaching. The data of this study which was based on the techniques of qualitative research was obtained from students attending third class of elementary mathemat ics teacher education program at a public university in the north of Turkey, in 2013-2014 academic year. As data colletion tool, five openended questions which were prepared by the researchers taking the opinions of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The reason why the pre-service teachers were interested and excited about Turkish-Islamic Scientists may be due to the fact that they did not have enough knowledge about scientists, research processes, and inventions of scientists. Studies have shown that the perceptions and knowledge of pre-service elementary teachers about scientists include stereotypes and are not based on a realistic basis (Çermik, 2013;Oğuz-Ünver, 2010). The research results indicate that adequate educational support should be provided not only in terms of the perception of scientists but also in terms of having knowledge about scientists.…”
Section: Discussionmentioning
confidence: 89%
“…The reason why the pre-service teachers were interested and excited about Turkish-Islamic Scientists may be due to the fact that they did not have enough knowledge about scientists, research processes, and inventions of scientists. Studies have shown that the perceptions and knowledge of pre-service elementary teachers about scientists include stereotypes and are not based on a realistic basis (Çermik, 2013;Oğuz-Ünver, 2010). The research results indicate that adequate educational support should be provided not only in terms of the perception of scientists but also in terms of having knowledge about scientists.…”
Section: Discussionmentioning
confidence: 89%
“…The results of studies on proof writing in geometry showed that students' proof writing skills were weak and they had difficulties (Daguplo, 2014;Güner & Topan, 2016;Şen & Güler, 2022). Güner and Topan (2016) revealed that primary school mathematics teacher candidates have weak geometric proof skills, they have difficulty in proving, they have misconceptions that a single example or numerical representation showing accuracy is sufficient for proof, and they cannot transfer their existing knowledge to the proof process. Şen and Güler (2022) examined the effectiveness of teaching activities based on the Van Hiele model on geometric proof writing skills.…”
Section: Proof Writingmentioning
confidence: 99%